Treatment of Habitual Patellar Dislocation in an Adult by Isolated Medial Patellofemoral Ligament Reconstruction - Yoann Bohu; Mathieu Thaunat; Nicolas Lefevre; Shahnaz Klouche; Serge Herman; Yves Catonné (Case Reports in Orthopedics)
Habitual patellar dislocations are rare in adults. Treatment is difficult, and often associated with significant morbidity. A 30-year-old man, construction worker, presented a habitual patellofemoral dislocation which was caused by direct trauma to the knee as a child. Clinical examination showed a 3 cm leg-length discrepancy with no rotational deformities. The patient had a limp and loss of function; the patella was dislocated laterally and had locked at 20° of flexion with a range of motion of 0°/0°/30°. Open surgery was performed associating lateral retinacular release, reconstruction of the medial patellofemoral ligament with an ipsilateral gracilis tendon graft. The postoperative course was simple with no complications. Four months after surgery the patient has begun working normally. At the final 50-month clinical follow-up, knee range of motion was 0°/0°/130°, and functional results were excellent on clinical assessment scores of Kujala, Lysholm, and subjective IKDC. MPFL reconstruction alone seems effective in habitual posttraumatic patellar dislocation in adults without any associated bone anomalies.